THE INFLUENCE OF EMOTIONAL INTELLIGENCE, SELF EFFICACY, AND COMPETENCE ON EMPLOYEE PERFORMANCE AT PT. LENGGA HARA MEDAN - Emy Yatul Hasanah; Nurmala; A Hadi Arifin; Marbawi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to analyze the influence of emotional intelligence, self-efficacy, and competence on employee performance at PT. Lengga Hara Medan. The method used in this study is a quantitative approach through multiple linear regression analysis. Data were collected using a questionnaire distributed to 83 respondents out of a total population of 500 employees, who are employees of PT. Lengga Hara Medan. The results of the study indicate that collectively (simultaneously) the independent variables, namely emotional intelligence, self-efficacy, and competence, have a significant influence on the dependent variable of employee performance. Partially, the independent variables of emotional intelligence, self-efficacy, and competence each have a positive and significant effect on the dependent variable of employee performance. Thus, the higher the emotional intelligence, self-efficacy, and competencies possessed by employees, the higher the performance produced by employees. The results of this study imply that companies must pay attention to the psychological and professional aspects of employees.